2022
DOI: 10.3389/fgene.2022.878618
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome/Exome Sequencing Uncovers Mutations and Copy Number Variations in Primary Diffuse Large B-Cell Lymphoma of the Central Nervous System

Abstract: Background/objective: Identification of key genetic alterations is of importance in the targeted therapies of primary central nervous system lymphoma (PCNSL). However, only a small number of studies have been carried out in PCNSL. In this study, we further described the genetic mutations and copy number variations (CNVs) in PCNSL patients using whole-genome/exome sequencing (WGS/WES), as well as revealed their associations with patients’ clinicopathological features and prognosis.Methods: Tumor specimens from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A possible explanation of these contradictory findings lies in the fact that the frequency of genetic alterations encompassing PD-1 ligands in PCNSL appears to be much lower than the one initially reported [38 ▪▪ ,68,69]. In addition, recurrent deletion of HLA genes [38 ▪▪ ,68,69] and presence of multiple inhibitory receptors on T cells infiltrating PCNSL [70] might represent additional reasons why T cells unleashed upon PD-1 blockade did yield the expected benefit.…”
Section: Novel Approaches For Relapsed/refractory Primary Central Ner...mentioning
confidence: 94%
See 1 more Smart Citation
“…A possible explanation of these contradictory findings lies in the fact that the frequency of genetic alterations encompassing PD-1 ligands in PCNSL appears to be much lower than the one initially reported [38 ▪▪ ,68,69]. In addition, recurrent deletion of HLA genes [38 ▪▪ ,68,69] and presence of multiple inhibitory receptors on T cells infiltrating PCNSL [70] might represent additional reasons why T cells unleashed upon PD-1 blockade did yield the expected benefit.…”
Section: Novel Approaches For Relapsed/refractory Primary Central Ner...mentioning
confidence: 94%
“…One of the major limitations of CAR-T cells therapy in PCNSL lies in the peculiar immunosuppressive tumour microenvironment (TME) leading to T cells exhaustion [69]; in this perspective, novel combination therapies with other agents, including checkpoint inhibitors, could potentially overcome the negative influence of TME and therefore increase antitumor efficacy of CAR-T cells. Moreover, combination with Ibrutinib might be investigated due to the encouraging data reported in CLL [84].…”
Section: Novel Approaches For Relapsed/refractory Primary Central Ner...mentioning
confidence: 99%
“…Chromosomal abnormalities included copy number gains of 2q37, 3q12.3, 7q, 11q, 9p24.1 (affecting CD274/PD-L1(programmed death-ligand 1) and PDCD1LG2/PD-L2(programmed death-ligand 2) ), 18q21 and chromosome 12, copy number deletions of 6p21–22 [human leukocyte antigen (HLA) locus], 6q21, 8q12, 9p21.3 ( CDKN2A biallelic loss), 19p13 ( CDKN2D ), and translocations of IgH-BCL6 [ 2 ▪▪ , 8 ▪▪ , 35 ▪ , 36 , 37 ].…”
Section: Molecular Profiles and Gene Expression Signatures Of Primary...mentioning
confidence: 99%
“…Focus to the most important gene mutations in PCNSLs: PIM1 gene mutations are described in 25--100% of cases [ 8 ▪▪ , 16 , 35 ▪ , 46 48 ]. Zhou et al [ 46 ] have divided CNS-DLBCL into two groups CDP ( PIM1 and/or CD79B mutations) and non-CDP (without PIM1 and CD79B mutations) with better outcome (long-term survival) observed for CDP group after high-dose methotrexate-based polychemotherapy.…”
Section: Molecular Profiles and Gene Expression Signatures Of Primary...mentioning
confidence: 99%
“…MYD88 L265P , is an important oncogene for lymphoma [ 324 327 ]. With the advancement of high-throughput molecular technologies, it has been found that mutations in the MYD88 L265P gene are present in 55–88% of patients with PCNSL [ 132 , 328 331 ]. Moreover, the protein expression of MYD88 was significantly elevated in PCNSL patients in comparison to individuals with lymphadenitis (70.18% vs. 15%) [ 58 ].…”
Section: Prognostic Markers For Pcnslmentioning
confidence: 99%